256 Slice Multi-detector Computed Tomography Thoracic Aorta Computed Tomography Angiography: Improved Luminal Opacification Using a Patient-Specific Contrast Protocol and Caudocranial Scan Acquisition. Issue 6 (November 2016) - Saade, Charbel; El-Merhi, Fadi; El-Achkar, Bassam; Kerek, Racha; Vogl, Thomas J.; Maroun, Gilbert Georges; Jamjoom, Lamia; Al-Mohiy, Hussain; Naffaa, Lena
Abstract : Clinical Relevance Statement: Caudocranial scan direction and contrast injection timing based on measured patient vessel dynamics can significantly improve arterial and aneurysmal opacification and reduce both contrast and radiation dose in the assessment of thoracic aortic aneurysms (TAA) using helical thoracic computed tomography angiography (CTA). Objectives: To investigate opacification of the thoracic aorta and TAA using a caudocranial scan direction and a patient-specific contrast protocol. Materials and Methods: Thoracic aortic CTA was performed in 160 consecutive patients with suspected TAA using a 256-slice computed tomography scanner and a dual barrel contrast injector. Patients were subjected in equal numbers to one of two contrast protocols. Patient age and sex were equally distributed across both groups. Protocol A, the department's standard protocol, consisted of a craniocaudal scan direction with 100 mL of contrast, intravenously injected at a flow rate of 4.5 mL/s. Protocol B involved a caudocranial scan direction and a novel contrast formula based on patient cardiovascular dynamics, followed by 100 mL of saline at 4.5 mL/s. Each scan acquisition comprised of 120 kVp, 200 mA with modulation, temporal resolution 0.27 seconds, and pitch 0.889:1. The dose length product was measured between each protocol and data generated were compared using Mann-Whitney U nonparametric statistics. Receiver operating characteristic analysis, visual grading characteristic (VGC), and κ analyses were performed. Results: Mean opacification in the thoracic aorta and aneurysm measured was 24 % and 55%, respectively. The mean contrast volume was significantly lower in protocol B (73 ± 10 mL) compared with A (100 ± 1 mL) ( P <0.001). The contrast-to-noise ratio demonstrated significant differences between the protocols (protocol A, 18.2 ± 12.9; protocol B, 29.7 ± 0.61; P < 0.003). Mean effective dose in protocol B (2.6 ± 0.4 mSv) was reduced by 19% compared with A (3.2 ± 0.8 mSv) ( P < 0.004). Aneurysmal detectability demonstrated significant increases by receiver operating characteristic and visual grading characteristic analysis for protocol B compared with A ( P < 0.02), and reader agreement increased from poor to excellent. Conclusions: Significant increase in the visualization of TAAs following a caudocranial scan direction during helical thoracic CTA can be achieved using low-contrast volume based on patient-specific contrast formula.